Tensioned fabric structures in jungle design shape - Min, Yee Hooi; Nur Afifi Zi,; Li-Sian, Tey; Syahrul Fithry Senin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Tensioned fabric structure became a topic of discussion for many engineers because of its lightweight. This structure manages to resist all loads such as wind and rain. Due to the light in weight, tensioned fabric structures are normally designed to be in the form of equal tensioned surface or minimal surface. The major objective of this study is to generate three Jungle forms with minimal surface or equal tensioned surface to apply in infrastructure and to propose an alternative for engineers to consider the Jungle minimal surface models. More study found out that minimal surface of tensioned fabric structure help in sustainability the environment. The form of tensioned fabric structure of this structure was applied using mathematical equation which was then generated through MATLAB. The three Jungle forms tensioned fabric structure show minimal surface. The study might inspire the engineers to implement Jungle shape in tensioned fabric structures.